EDUCATIONAL HONESTY IN ACEH-INDONESIA: THE MAIN PHILOSOPHICAL VALUE IN SCHOOL - Suud, Fitria M.; Sutrisno, Sutrisno; Madjid, Abd. (AIUA Journal of Islamic Education, 2019)
This study aims to explore the honesty education developed by Sukma Bangsa Pidie School, which has been known as an honest school in Aceh, Indonesia. The focus of this research is to discover the philosophical values and concepts of honesty education built by schools to cultivate honesty in all school community. This research employed a qualitative method by using the case study approach. The results of this research showed that honesty education could work well because philosophical values were built based on normative, academic and professional values. This philosophical value was instilled for students and for the entire school community. Furthermore, the concept of honesty education was generated in three stages, starting from foundation, school and grade level. The concept of honesty education become stronger because it was derived from the Vision, Mission, Objectives and School Programs. This research is expected to offer a new concept of honesty education in Indonesia.